# Solve for w 12-3(2w+7)=7w-3(7+w)

12-3(2w+7)=7w-3(7+w)
Since w is on the right side of the equation, switch the sides so it is on the left side of the equation.
7w-3(7+w)=12-3(2w+7)
Simplify 7w-3(7+w).
Simplify each term.
Apply the distributive property.
7w-3⋅7-3w=12-3(2w+7)
Multiply -3 by 7.
7w-21-3w=12-3(2w+7)
7w-21-3w=12-3(2w+7)
Subtract 3w from 7w.
4w-21=12-3(2w+7)
4w-21=12-3(2w+7)
Simplify 12-3(2w+7).
Simplify each term.
Apply the distributive property.
4w-21=12-3(2w)-3⋅7
Multiply 2 by -3.
4w-21=12-6w-3⋅7
Multiply -3 by 7.
4w-21=12-6w-21
4w-21=12-6w-21
Subtract 21 from 12.
4w-21=-6w-9
4w-21=-6w-9
Move all terms containing w to the left side of the equation.
Add 6w to both sides of the equation.
4w-21+6w=-9
10w-21=-9
10w-21=-9
Move all terms not containing w to the right side of the equation.
Add 21 to both sides of the equation.
10w=-9+21
10w=12
10w=12
Divide each term by 10 and simplify.
Divide each term in 10w=12 by 10.
10w10=1210
Cancel the common factor of 10.
Cancel the common factor.
10w10=1210
Divide w by 1.
w=1210
w=1210
Cancel the common factor of 12 and 10.
Factor 2 out of 12.
w=2(6)10
Cancel the common factors.
Factor 2 out of 10.
w=2⋅62⋅5
Cancel the common factor.
w=2⋅62⋅5
Rewrite the expression.
w=65
w=65
w=65
w=65
The result can be shown in multiple forms.
Exact Form:
w=65
Decimal Form:
w=1.2
Mixed Number Form:
w=115
Solve for w 12-3(2w+7)=7w-3(7+w)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top